Neuroprotective effect of Astragali Radix on cerebral infarction based on proteomics - Li, Ying; Wang, Daoping; Guo, Rongjuan; Ma, Bo; Miao, Lan; Sun, Mingqian; He, Lijuan; Lin, Li; Pan, Yinghong; Ren, Junguo; Liu, Jianxun (Frontiers in Pharmacology, 2023)
Objective: Astragali Radix (AR, Huangqi in Chinese) has a neuroprotective effect on cerebral infarction (CI). In order to explore the biological basis and therapeutic mechanism of AR in CI, a double-blind randomized controlled trial was established in this study, and proteomics analysis was carried out on serum samples of patients. Methods: The patients were divided into the AR group (n = 35) and the control group (n = 30). The curative effect was evaluated by the traditional Chinese medicine (TCM) syndrome score and clinical indicators, and the serum of the two groups was analyzed by proteomics. Based on bioinformatics analysis methods, the changes in differential proteins between two groups of samples were explored, and the key proteins were validated through enzyme-linked immunosorbent assay (ELISA). Results: The results of this study showed that the scores of deficiency of vital energy (DVE), blood stasis (BS), and NIH Stroke Scale (NIHSS) decreased significantly (p < 0.05), while the scores of the Barthel Index (BI) increased, indicating that AR could significantly improve the symptoms of CI patients. In addition, we found that compared with the control group, AR upregulated 43 proteins and downregulated 20 proteins, especially focusing on anti-atherosclerosis and neuroprotective effects. Moreover, ELISA indicated the levels of IL-6, TNF-α, VCAM-1, MCP-1, and ICAM-1 were significantly decreased in the serum of the AR group (p < 0.05, p < 0.01). Conclusion: This study found that AR can significantly recover the clinical symptoms of CI. Serum proteomics research results show that AR may act on IL-6, TNF-α, VCAM-1, MCP-1, and ICAM-1, and play anti-atherosclerosis and neuroprotective roles. Clinical Trial Registration: [clinicaltrials.gov], identifier [NCT02846207]